Assessment of self-assertiveness among faculty nursing students in Tishreen University (Descriptive research) - Hammoud, Solaf; Dawod, Lobnah; Keheli, Ola (Latakia University Journal -Medical Sciences Series, 2018)
This research aimed to assess self- assertiveness level among faculty nursing students in Tishreen University. The research sample consisted of 400 randomly selected students of nursing faculty in the four academic years, who were available during the period of data collection. Assessment of self- assertiveness tool has been translated by the researcher, and consisted of 28 questions measuring how a person behaves in different situations such as the ability to deal with criticism, meeting others and spontaneous expression of feelings. Basic results showed that self- assertiveness level was moderate among more than three quarters of the sample and it increased with the progress of the academic year, the increase in parents’ educational level and the increase in family income. تقييم توكيد الذات لدى طلاب كلية التمريض في جامعة تشرين (بحث وصفي) هدف البحث إلى تقييم مستوى توكيد الذات لدى طلاب كلية التمريض في جامعة تشرين. حيث تكونت عينة البحث من 400 طالب/ة، أخذت عشوائياً من طلاب كلية التمريض في السنوات الأكاديمية الأربعة، ممن تواجدوا أثناء فترة تجميع البيانات. تم ترجمة أداة تقييم توكيد الذات من قبل الباحثة إلى اللغة العربية، وتكونت الأداة من 28 سؤالاً يقيس كيفية تصرف الشخص في المواقف المختلفة كالقدرة على التعامل مع النقد، مواجهة الآخرين، قول لا للطلبات غير المعقولة، القدرة على السؤال وطلب المساعدة، الاعتذار، القدرة على التعامل مع المجاملة، القدرة على التعبير عن الرأي والتعبير العفوي عن المشاعر. كانت أهم النتائج أن مستوى توكيد الذات متوسط لدى أكثر من 75% من العينة ويزداد مع التقدم في السنة الدراسية، ارتفاع المستوى التعليمي للوالدين وزيادة دخل الأسرة.